Persepsi Karyawan terhadap Pengelolaan Lingkungan dan Persepsi Masyarakat terhadap Kualitas Lingkungan pada Industri Semen Pasca Implementasi AMDAL dan ISO 14001 - Lestari, Febrianti (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2011)
Cement industry based on in its production process is categorized as industries that significantly pollute the environment, as well as a source of environmental degradation in the surrounding areas. In this regard, PT Indocement Tunggal Prakarsa Tbk. (PT.ITP) has conducted an AMDAL study and has implemented an international standard, Environmental Management System ISO 14001, as an effort to mitigate and prevent environmental pollution and degradation. This research is aimed at employed dan community perception of environmental management for implemented by PT.ITP as required in the AMDAL documents and ISO 14001 requirements. The results of this research indicated that environmental management activities for PT.ITP’s employee perception of the AMDAL implementation considered at a low level, while their perception of the EMS implementation is considered a high level. Community perception of the environmental quality related to management effort implemented by PT.ITP during 2002-2004 indicated that current environmental quality is better compared with the previous condition.